PENGARUH STRUKTUR KEPEMILIKAN TERHADAP AGRESIVITAS PAJAK - Dian Anggraeni Pratiwi; Moh Didik Ardiyanto (Diponegoro Journal of Accounting, 2018)
This study aims to examine empirically: 1) the effect of state ownership on tax aggresiveness, 2) the effect of ownership concentration on tax aggresiveness, 3) the effect of institutional ownership on tax aggresiveness. This study used an abnormal book-tax difference (ABTD) and effective tax rate (ETR) as a proxy of tax aggresiveness.The population in this research is manufacturing company listed in BEI period 2012-2016. Samples are selected using the purposive sampling method. The multiple linear regression is used to test the hipotheses. The results of this study show that state ownership has a significant positive effect to the tax aggresiveness with ABTD proxy, ownership concentration has a significant positive effect to the tax aggresiveness with  ABTD proxy, and institutional ownership has a significant negative effect to the tax aggresiveness with ABTD  proxy.